2013
DOI: 10.1007/s12519-013-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children with chronic viral hepatitis: what is available and what is in store

Abstract: The results of reported studies confirmed that at least some of the new drugs, with greater efficacy and/or minor side-effects, will be used clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 60 publications
0
10
0
3
Order By: Relevance
“…ETV is a recently approved drug to treat pediatric CHB and has shown potent antiviral effects, low drug resistance and tolerable side effects. 11 14 15 16 17 In an adult study, Chang et al 13 reported the superiority of ETV to LAM in HBeAg-positive CHB, with histologic and HBV DNA level improvement and ALT normalization at 48 weeks. Another adult study comparing ETV vs. LAM therapy for naïve patients with spontaneously reactivated CHB presenting as acute-on-chronic liver failure showed that ETV significantly reduced HBV DNA titers, improved Child-Turcotte-Pugh and model for end-stage liver disease scores and extended long-term survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ETV is a recently approved drug to treat pediatric CHB and has shown potent antiviral effects, low drug resistance and tolerable side effects. 11 14 15 16 17 In an adult study, Chang et al 13 reported the superiority of ETV to LAM in HBeAg-positive CHB, with histologic and HBV DNA level improvement and ALT normalization at 48 weeks. Another adult study comparing ETV vs. LAM therapy for naïve patients with spontaneously reactivated CHB presenting as acute-on-chronic liver failure showed that ETV significantly reduced HBV DNA titers, improved Child-Turcotte-Pugh and model for end-stage liver disease scores and extended long-term survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of LAM treatment is the need for prolonged treatment, which leads to higher resistance rates. 6 9 10 11 20 In a pediatric multicenter trial, 19% of children undergoing 52 weeks of LAM therapy developed codon changes in the YMDD (tyrosine-methionine-aspartate-aspartate) motif of the HBV polymerase gene. 21 In contrast, ETV exhibited lower resistance rates in a pediatric clinical trial (0.6% at 1 year of treatment and 2.6% at 2 years of treatment).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paucity of pharmacokinetic, efficacy, and safety data in children is one of three issues in treatment of CHC in children. 3 , 52 A second issue is the lack of consensus regarding which patients and when to treat, which is an issue that is likely to remain even after the first is resolved. 3 The lack of data and lack of consensus on whom to treat are inter-related problems because without a defined treatment population it is difficult to design a robust trial.…”
Section: Discussionmentioning
confidence: 99%